Clinical efficacy of SGLT2 inhibitors with different SGLT1/SGLT2 selectivity in cardiovascular outcomes among patients with and without heart failure: A systematic review and meta-analysis of randomized trials. Issue 51 (23rd December 2022) - Lee, Mei-Chuan; Hua, Yi-Ming; Yang, Chun-Ting; Kuo, Fang-Hsiu; Chang, Wei-Ting; Tang, Hsin-Ju; Siong Toh, Han; Lin, Yu-Min; Chen, Sih-Yao; Chang, Hung-Yu; Liao, Chia-Te
Abstract : Background: Some sodium-glucose co-transporter-2 (SGLT2) inhibitors showed benefits on heart failure (HF), but different SGLT2/SGLT1 selectivity might influence the treatment effect. This study aimed to meta-analyze the treatment effects of SGLT2 inhibitors and the diversity of receptor selectivity for patients with and without HF. Methods: Randomized controlled trials were searched in PubMed, Embase, Cochrane databases and ClinicalTrials.gov registry from inception to October 2020. The interest outcomes were analyzed with random-effects models and presented with a risk ratio (RR) and 95% confidence interval (CI). Subgroup analyses examined the treatment effects among SGLT2 inhibitors with different SGLT2/SGLT1 selectivity. Results: The final analyses included 10 trials and 52, 607 patients. The RR of total cardiovascular (CV) death or hospitalization for HF (HHF) between SGLT2 inhibitors and placebo was 0.79 (95% CI 0.74–0.84, I 2  = 31%). With SGLT2 inhibitors, HF patients had reduced mortality risks (RR 0.89, 95% CI 0.80–0.99, I 2  = 0), and non-HF patients had lower risks of major adverse CV events (RR 0.92, 95% CI 0.85–0.99, I 2  = 0). The risk reduction of HHF was consistent in groups of HF (RR 0.72, 95% CI 0.64–0.80, I 2  = 8%) and non-HF (RR 0.74, 95% CI 0.61–0.89, I 2  = 0), but the effect of the low SGLT2/SGLT1 selectivity inhibitor was insignificant in non-HF patients. Conclusion: The efficacy of SGLT2 inhibitors on risk reduction of total CV death or HHF is consistent with the previous studies. The regimen is beneficial for reducing mortality in patients with HF and major adverse CV events in those without HF. Different SGLT2/SGLT1 selectivity may differ in the treatment effects in patients with and without HF.